SERUM VITAMIN D AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - AHMED, SHWAN SULAIMAN (Fırat Üniveristesi, 2020)
Amaç: Vit D eksikliği, insulin direncinde etken ve Type 2 diyabetik mellitus hastalığı riskini artıran yaygın bir sağlık sorunudur. T2DM'l olan hastalarda serum D vitamin düzeylerinde bakılarak Ca ve Mg emilimindeki rolü ve önemi araştırtırıldı. Serum D vitamini, Mg, Ca, kolesterol, trigliserit değelendirildi. Gereç ve Yöntem: Bu çalışma Irak'ın Duhok şehrinde bulunan Azadi Eğitim Hastanesi Endokrin ve Diyabet Ünitesinde yapıldı. Bu çalışma 95 denek, 70'i T2DM hastası, HDL, LDL ve FBS, oto analizör Cobas 6000 kullanılarak ölçüldü. Glikatlı hemoglobin (HPLC D10) oto analizör cihazı ile yapıldı. Bulgular: T2DM'li hastalarda serum vit D düzeyi kontrol gubundan istatiksel anlamda önemli derecede düşüktü. Açlık kan şekeri ile D vitamini ve HbA1C arasındaki ilişki istatistiksel olarak anlamlı bulundu. Ayrıca vit D ile Ca ve Mg arasında da anlamlılık gözlendi. Sonuç: Açlık kan şekerinde artışla vit D eksikliği T2DM hastalarında HbA1C değerindeki bu anlamlılık sonucunda T2DM hastalarında Vit D değerinin periyodik olarak ölçmesinin gerekliliği vurgulanmalıdır. Vit D, Ca ve Mg 'un bağırsak emilimini arttırmaktan sorumludur. Vit D eksikliği olan T2DM hastalarında Ca ve Mg değerlerini periyodik olarak ölçülmesi oldukça önemlidir.

Background: Vit D deficiency is a common health problem that increases the risk of Type 2 diabetic mellitus disease T2DM. Serum vitamin D care and the importance of Ca and Mg absorption were investigated. Serum vitamin D, Mg, Ca, cholesterol, triglyceride were evaluated. The role and importance of vitamin D in Ca and Mg absorption was evaluated by looking at vitamin D in patients with diabetic mellitus Type 2. Materials and Methods: This study was done in the Azadi Education Hospital Endocrine and Diabetes Unit in Duhok, Iraq. This study was measured using 95 subjects, 70 patients with T2DM, HDL, LDL and FBS, auto analyzer Cobas 6000. Glycated hemoglobin (HPLC D10) was made with an auto analyzer device. Results: Results: In patients with T2DM, serum vit D level was significantly lower than the control group. The relationship between fasting blood sugar and vitamin D and HbA1C was found statistically significant. There was also a significant difference between vit D and Ca and Mg. Conclusion: As a result of high significant between Vit-D deficiency with increase in fasting blood glucose and HbA1C value of T2DM patient and the role of Vit-D in insulin resistance, T2DM patient should measure their Vit-D value periodically. Vit D is responsible for increasing intestinal absorption of Ca and Mg. It is very important to periodically measure Ca and Mg values in T2DM patients with Vit D deficiency.
Diyabet mellitus tip 2'li hastalarda serum vitamin D'nin incelenmesi
Keywords: Biyokimya